THE ROLE OF MRI IN DIAGNOSING NEUROLOGICAL DISORDERS - Mohammed Abdulaziz Al Qahtani, Moayad Alwi Abdalwahed; Noura Saud Alonizi (Chelonian Research Foundation, 2025)
Magnetic resonance imaging (MRI) has become an indispensable tool in the diagnosis and management of neurological disorders. Ischemic stroke, hemorrhagic stroke, multiple sclerosis, Alzheimer’s disease, and brain tumors are examples of conditions for which MRI scans provide crucial clinical information. MRI produces images by subjecting the body to a magnetic field, and then using radio-frequency pulses to stimulate the emission of energy from atomic nuclei. The resulting signals are used to reconstruct images that encode structural or functional information about the brain. Structural scans visualize the anatomy in cross-section at high resolution. Functional MRI (fMRI) renders maps of cerebral activity and metabolism. Diffusion tensor imaging (DTI) tracks the flow of water molecules along the white-matter tracts and thereby reveals connective pathways.